Interval prediction of order statistics and record values using concomitants of order statistics and record values for Morgenstern family of distributions - Muraleedharan, Laji; Chacko, Manoj (Journal of Statistical Research, 2023)
In this paper, we discuss the problem of predicting intervals for future order statistics and k-record values based on observed concomitants of order statistics and observed concomitants of k-record values arising from a Morgenstern family of distributions. The coverage probabilities obtained are accurate and independent of the parent distribution. A real data set is also considered to exemplify the proposed methodologies developed in this paper. Journal of Statistical Research 2022, Vol. 56, No. 1, pp. 55-72